Knowledge management : case study on NCS Pte Ltd. - Lim, Eu Ming. (2008)
This paper discusses the factors that are critical to the success of knowledge management in organizations based on a case study of NCS Pte Ltd. The study identified four factors that are critical to the success of knowledge management initiatives, of which culture is the most important.